Business Ethics and Critical Consultant Jokes: New Research Methods to Study Ethical Transgressions - Bouwmeester, Onno (SpringerBriefs in Ethics, 2023)
This open access book offers four ways to enrich traditional research methods in business ethics. By looking at critical jokes and cartoons on management consultants, their business practice and their clients’ demands, many ethical transgressions in business get addressed. By illustrating and criticizing such transgression, jokes can serve as an example in a theoretical argument, as a prompt to reflect on in an open interview, as a statement to assess in an enquiry or as basis for qualitative content analysis. By adding jokes to the conversation on ethical transgressions in business much depth and honesty can be added, resulting in better research data. Jokes can help to surpass social desirability bias included in answers given in traditional interview settings or enquiries. This book is of interest to consultants, researchers, educators and students in business ethics and management. The book showcases what kind of practical and ethical wisdom is embedded in business jokes and how this knowledge can be made productive in the context of business ethics.